1998
DOI: 10.1016/s0014-5793(97)01528-7
|View full text |Cite
|
Sign up to set email alerts
|

Yeast RNase H(35) is the counterpart of the mammalian RNase HI, and is evolutionarily related to prokaryotic RNase HII1

Abstract: We cloned the Saccharomyces cerevisiae homologue of mammalian RNase HI, which itself is related to the prokaryotic RNase HII, an enzyme of unknown function and previously described as having minor activity in Escherichia coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 30 publications
(30 reference statements)
2
44
0
Order By: Relevance
“…In vivo, FEN1-directed RNA removal may be only one of several redundant pathways. Previous studies indicated that RNase H is responsible for RNA primer removal (42), but recent genetic studies show that the deletion of the RNase H catalytic subunit did not affect cell viability in yeast (43). This suggests that other enzymes are also involved in RNA removal, one of which is Dna2p.…”
Section: Discussionmentioning
confidence: 98%
“…In vivo, FEN1-directed RNA removal may be only one of several redundant pathways. Previous studies indicated that RNase H is responsible for RNA primer removal (42), but recent genetic studies show that the deletion of the RNase H catalytic subunit did not affect cell viability in yeast (43). This suggests that other enzymes are also involved in RNA removal, one of which is Dna2p.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, more recent studies have indicated that the major in vitro mechanism for RNA primer removal is flap processing by Rad27/FEN1 and Dna2 (14)(15)(16), with Exo1 apparently being able to substitute for Rad27/FEN1 in S. cerevisiae (17,18). Because RNase H2 is not essential in S. cerevisiae (19), it is possible that RNase H2 plays either a redundant or a stimulatory role in Okazaki fragment processing, which could underlie the substantial growth defects caused by combining mutations affecting RNase H2 with mutations affecting Rad27/Fen1 (7,(20)(21)(22)(23).…”
mentioning
confidence: 98%
“…In addition, RNase HI may be involved in Okazaki fragment processing, since in vitro it preferentially cleaves 5Ј to the last ribonucleotide of an RNA-DNA junction to remove an RNA primer (9,62). Rnh35, the catalytic subunit of the yeast homolog of mammalian RNase HI, may work cooperatively with Rad27 to remove RNA primers, since Rad27 preferentially cleaves a single-stranded flap of RNA or DNA, whereas yeast RNase H (35) can cleave RNA hybridized to DNA (24,68). Unlike a rad27⌬ strain, rhn35⌬ cells have a normal growth rate.…”
mentioning
confidence: 99%